2017
DOI: 10.1561/106.00000008
|View full text |Cite
|
Sign up to set email alerts
|

It’s All About Information? The Following Behaviour of Professors and PhD Students in Computer Science on Twitter

Abstract: Article available under the terms of the CC BY-NC-ND 2.0 licence (https://creativecommons.org/licenses/by-nc-nd/2.0/) eprints@whiterose.ac.uk https://eprints.whiterose.ac.uk/ Reuse Unless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 50 publications
0
14
0
2
Order By: Relevance
“…The study of Kennedy, Wellman, and Klement [21] suggested that women are more inclined to online networking and that the female internet use can be characterized in accordance with the traditional role of females as "caregiver", i.e., more cooperative and more directed to social interaction. Similarly, also for the academic use of Twitter there is first evidence for gender-related differences [22].…”
Section: Gender-related Differences In Academia Communication and Somentioning
confidence: 99%
“…The study of Kennedy, Wellman, and Klement [21] suggested that women are more inclined to online networking and that the female internet use can be characterized in accordance with the traditional role of females as "caregiver", i.e., more cooperative and more directed to social interaction. Similarly, also for the academic use of Twitter there is first evidence for gender-related differences [22].…”
Section: Gender-related Differences In Academia Communication and Somentioning
confidence: 99%
“…Similarly, the perceived informativeness of a Twitter account has been shown to reduce the likelihood of unfollowing [14]. Recent research has developed more detailed conceptualizations of motives for the professional and academic usage of social media [15] [16]. For example, based on an online survey among members of three professional social science organizations, Gruzd and Goertzen [16] identified distinct motives for social media usage such as "keeping up to date with topics", "following other researchers' work" and "discovering new ideas or publications".…”
Section: Motives For Social Media Use In Academiamentioning
confidence: 99%
“…She found that perceived benefits included connecting and establishing networks with other academics as well as non-academic audiences, promoting openness and sharing of information, publicizing and development of research, and giving and receiving support. Another study by Linek and colleagues [15] showed that (strategic) politeness can also be part of work-related community development and academic networking on Twitter.…”
Section: Motives For Social Media Use In Academiamentioning
confidence: 99%
“…The microblogging service Twitter supports a number of uses in an academic context, such as information seeking, relationship management, and signaling affinity to particular issues and people [14]. Prior research [15] has shown that Twitter usage among computer scientists is predominantly motivated by information seeking, with community development playing an important role as well. With respect to reciprocal relationships, it should be noted that following a Twitter account provides other gratifications than following back.…”
Section: Motives For Academic Twitter Use: the Uses And Gratificationmentioning
confidence: 99%
“…For this study we use a dataset of Twitter accounts of computer scientists [22] dataset available on: http://dx.doi.org/10.5281/zenodo.12942). The dataset has previously been used for a study of academic Twitter use motives among computer scientists [15] and provided evidence that for this audience, Twitter is primarily an information network, but also delivers community development gratifications. In this study, we used the dataset to investigate gender differences in the social networking behavior of computer scientists (professors and PhD students).…”
Section: Gender Gap In Science and Gender-specific Media Usagementioning
confidence: 99%